RENCANA PENGELOLAAN PARTISIPATIF OBJEK GEOWISATA TEBING KOJA (STUDI KASUS: TEBING KOJA, DESA CIKUYA, KECAMATAN SOLEAR, KABUPATEN TANGERANG) - Sandra Soraya; Parino Rahardjo; Suryono Herlambang (Jurusan Arsitektur dan Perencanaan, 2020)
Tebing Koja tourism object has a geotourism attraction that attracts tourists and can give someone's curiosity because it has another designation that is